Energy as a main driver of Qatari foreign policy (Comillas Journal of International Relations, 2016)
Qatar is one of the smallest countries in the world with approximately a quarter million of native population. Despite these geographical and demographic limitations, Doha has established itself as a major player on both regional and international scenes. A major drive behind this ascendancy is the accumulation of massive oil and natural gas revenues. This essay examines the role hydrocarbon assets have played in the internal and external transformation of Qatari policy and the proposed strategies to mitigate the impact of the sharp drop in oil prices since June 2014.
Keywords: Qatar; foreign policy; fossil fuels; liquefied natural gas (LNG); shale gas; energy exports; diversification; Qatar Investment Authority